2020
DOI: 10.18316/sdh.v8i1.6038
|View full text |Cite
|
Sign up to set email alerts
|

Ações manipulativas e o ato de criar brincadeiras com cubos em crianças com e sem baixa visão

Abstract: Objetivo: identificar e descrever as ações manipulativas e as brincadeiras criadas pelas crianças com e sem baixa visão em idade escolar, durante o brincar com cubos de diferentes estímulos.Métodos: participaram sete crianças com e sem baixa visão (8,8 anos±1,02), as mesmas foram filmadas durante o brincar com seis cubos: transparente, preto, alto contraste, luminoso, auditivo e estímulo tátil. A ordem da entrega foi randomizada e a permanência com cada cubo foi de 40 segundos (intervalo de 10 segundos entre e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 9 publications
0
5
0
17
Order By: Relevance
“…This research adopted the same methodology used in the study by Oliveira et al 6 During the evaluation, cubes with the following specifications were used: six cubes 15 cm, 410 g (Figure 1): (A) transparent cube (plain acrylic); (B) black cube (non-contrast); (C) high-contrast cube (with different shaped stimuli in black and white); (D) light stimulus cube (two transparent sides, with a light source inside the cube = the other sides were colored in yellow, blue, green and red); (E) auditory stimulus cube (with a rattle inside and covered with light gray paper) and (F) tactile stimulus cube (each side have a texture of different materials, including soft, wavy (narrow and broad), rough and wrinkly).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research adopted the same methodology used in the study by Oliveira et al 6 During the evaluation, cubes with the following specifications were used: six cubes 15 cm, 410 g (Figure 1): (A) transparent cube (plain acrylic); (B) black cube (non-contrast); (C) high-contrast cube (with different shaped stimuli in black and white); (D) light stimulus cube (two transparent sides, with a light source inside the cube = the other sides were colored in yellow, blue, green and red); (E) auditory stimulus cube (with a rattle inside and covered with light gray paper) and (F) tactile stimulus cube (each side have a texture of different materials, including soft, wavy (narrow and broad), rough and wrinkly).…”
Section: Methodsmentioning
confidence: 99%
“…Sensorial stimuli are essential to arouse the child's curiosity, encourage manipulating objects, and create games. Oliveira et al 6 study has shown that, while manipulating sensorial cubes, children can imagine games, for instance, the luminous cube was compared to a lampshade in a playhouse, and the cube with auditory stimulation could be used to make music and play basketball. It is noticeable that the imagination allows the child to create different meanings for the same object, whether to interact with a friend or to play by themselves 7 , being an important mediator for child development and perception of the self as a whole 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As ações motoras contabilizadas em cada cubo fazem parte de dois estudos 13,14 . As novas ações apresentadas no estudo: Ações manipulativas e o ato de criar brincadeiras com cubos em crianças com e sem baixa visão, estão na tabela abaixo (Quadro 1).…”
Section: Métodounclassified
“…Representação dos cubos. Uberaba, 2020.Legenda: A: cubo transparente; B: cubo preto; C: cubo alto-contraste; D: cubo luminoso; E: cubo auditivo; F: cubo tátil Fonte: Oliveira C, Silva PQN, Pelizaro BP, Pereira K, 202014 .…”
unclassified
“…O estudo mais recente identificou e descreveu as ações manipulativas e as brincadeiras criadas pelas crianças com e sem baixa visão dos 7 aos 10 anos de idade, durante o brincar com cubos de diferentes estímulos (transparente, preto, alto contraste, luminoso, auditivo e estímulo tátil) (figura 2). As autoras verificaram que as crianças realizaram 14 tipos de ações manipulativas, em que as principais brincadeiras criadas foram a de montar formas com os cubos e empilhá-los 31 Os estudos realizados até o momento contribuíram de forma significativa para o conhecimento das características motoras, funcionais e ambientais da criança com deficiência visual, bem como para a adaptação de escalas que proporcionam a avaliação adequada para essa população. O conhecimento sobre formas de avaliação é essencial para identificar precocemente o melhor estímulo a ser utilizado durante o tratamento com essas crianças.…”
Section: Relatos Dos Estudos Realizados Em Crianças Com Baixa Visãounclassified